2017
DOI: 10.2341/16-108-l
|View full text |Cite
|
Sign up to set email alerts
|

Grinding With Diamond Burs and Hydrothermal Aging of a Y-TZP Material: Effect on the Material Surface Characteristics and Bacterial Adhesion

Abstract: The aim of this study was to evaluate the effect of grinding with diamond burs and low-temperature aging on the material surface characteristics and bacteria adhesion on a yttrium-stabilized tetragonal zirconia polycrystalline (Y-TZP) surface. Y-TZP specimens were made from presintered blocks, sintered as recommended by the manufacturer, and assigned into six groups according to two factors-grinding (three levels: as sintered, grinding with extra-fine diamond bur [25-μm grit], and grinding with coarse diamond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
0
23
0
3
Order By: Relevance
“…Microbiological tests were performed on different ceramic materials, including feldspathic ceramics, 8,22,40,43 zirconia, 20–22,29–31,34–36,38,39,41,42,44,45 zirconia‐reinforced lithium silicate, 30,41 aluminum‐zirconia, 20,22,31 aluminum, 33 leucite, 11,33,41 lithium disilicate, 11,20,31,34,37,41,44 vitreous ceramics 20,31 and fluorapatite veneering porcelain 32 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbiological tests were performed on different ceramic materials, including feldspathic ceramics, 8,22,40,43 zirconia, 20–22,29–31,34–36,38,39,41,42,44,45 zirconia‐reinforced lithium silicate, 30,41 aluminum‐zirconia, 20,22,31 aluminum, 33 leucite, 11,33,41 lithium disilicate, 11,20,31,34,37,41,44 vitreous ceramics 20,31 and fluorapatite veneering porcelain 32 …”
Section: Resultsmentioning
confidence: 99%
“…The included studies measured the roughness by confocal laser microscope, 41,44 roughness analyzer/contact rugosimeter, 8,22,30,39,40 profilometer, 31–34,36,37,43 optical interferometer, 45 and atomic force microscopy 21,29,38,42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Deville et al indicated that the aging kinetics of zirconia is critically influenced by the surface stress state, and the tetragonal to monoclinic transformation preferentially occurs on neighboring areas of residual stress concentration [6,32]. Thus, it can be assumed that the effects of LTD (i.e., grain pullout) on the zirconia surface first occur in the proximity of grains with the highest topography (superficial layer), where an uneven distribution of stress is most likely to co-exist with increased susceptibility to water contact, resulting in reduced surface roughness compared to non-aged zirconia [32,33]. With increasing aging time, phase transformation is extended to the entire surface and inside the crystal grain via a nucleation and growth mechanism, yielding Ra values comparable to those of non-aged samples [6,9,32].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicamente, o aumento da rugosidade superficial em mais de 0,2 µm têm sido associado ao acúmulo de biofilme e consequentemente, ao aumento do risco à carie e à inflamação periodontal, se a peça protética estiver exposta no ambiente bucal (Bollen et al, 1997). Entretanto, Dutra et al (2017) Alguns estudos constataram que o aumento da rugosidade superficial pode provocar a diminuição da resistência à flexão da zircônia (Kosmac et al, 2008;Iseri et al, 2010;Canneto et al, 2016), enquanto alguns estudos não encontraram esta correlação (Curtis et al, 2006;Subasi et al, 2014;Preis et al, 2015;Lee et al, 2016;Hatanaka et al, 2016;Pereira et al, 2015;Khayat et al, 2017;Ozer et al, 2017) e outros afirmaram que pode haver o aumento da resistência à flexão (Ho et al, 2009;Pereira et al, 2016A;Ramos et al, 2016). Outra propriedade que possui relação com a resistência e comportamento mecânico dos materiais dentários é o módulo de elasticidade.…”
Section: Os Maiores Valores De Rugosidade Superficial Foram Obtidos Nunclassified